Management of a rare case of isolated U-shaped displaced sacral fracture in a young female high school student. (August 2022) - Kanaan, Tareq; Alisi, Mohammed; Hijazein, Yazan; Naneh, Yazan; Kheshman, Abdallah; Hadadin, Hiba; Dahabreh, Dina; Hadidi, Fadi; Al-Sabbagh, Qussay
Abstract: Sacral fractures in young healthy patients are usually linked to high-energy trauma. They are often associated with multiple other injuries. Isolated sacral fractures are rare and can be easily missed in the absence of other surrounding pelvic or spinal injuries. In this article, we present a rare case of isolated U-shaped displaced sacral fracture despite the high-energy mechanism of injury being missed on initial presentation. This is a 17-year-old healthy female who presented to the emergency department after falling from five-meter height. She complained of lower back pain and inability to ambulate. Physical examination revealed significant sacral tenderness, bilateral lower limb weakness and hypoesthesia, anesthesia of the saddle area, weak anal tone and absent anal reflex. Initial radiographs showed no apparent fractures. Further imaging by pelvic computed tomography, however, revealed an isolated U-shaped displaced sacral fracture. The patient was treated by decompression and lumbopelvic fixation by triangular osteosynthesis and iliosacral screw. This fixation method restored stability of the spinopelvic junction and allowed for early mobilization. At her 18-month follow-up visit, she showed minimal disability score (10%) on the Oswestry Disability Index. In conclusion, sacral fractures are considered exceedingly rare to occur in isolation and in young healthy patients.